The time course of emotional picture processing: an event-related potential study using a rapid serial visual presentation paradigm - Zhu, Chuanlin; He, Weiqi; Qi, Zhengyang; Wang, Lili; Song, Dongqing; Zhan, Lei; Yi, Shengnan; Luo, Yuejia; Luo, Wenbo (Frontiers in Psychology, 2015)
Rapid recognition of the emotional significance of visual stimuli plays an important role in our daily life. The present study recorded event-related potentials with rapid serial visual presentation (RSVP) paradigm to explore the time course of processing of emotionally charged pictures (“emotional pictures”). Participants completed a dual-target task as quickly and accurately as possible, in which they were asked to judge the valence (positive, neutral, or negative) of the given picture and the gender of the person depicted. The results showed that the amplitudes of P2 were larger for emotional pictures than for neutral pictures and therefore represents brain processes that distinguish emotional stimuli from non-emotional. Furthermore, the amplitudes of the late positive potential elicited by positive, neutral, and negative pictures differ from each other, implicating this component in brain processes that discriminate different types of emotion. Additionally, the time course of the processing of emotional pictures was consistent with the latter two stages of a three-stage model derived from studies of emotional facial expressions processing and emotional adjectives processing. This indicated that in late perceptual and early cognitive processing, the processes by which the same emotion is conveyed by different types of material are similar, when attentional resources are limited.